Renal Flare as a Predictor of Incident and Progressive CKD in Patients with Lupus Nephritis - Parikh, Samir V. (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: Renal flares are common in lupus nephritis. The impact of flares on the development of CKD in lupus nephritis was examined. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: A retrospective analysis of prospectively collected data from the Ohio Systemic Lupus Erythematosus (SLE) Study was conducted to determine if renal flares predispose to new CKD or progression of preexisting CKD. Patients in the Ohio SLE Study were followed from 2001 to 2009, with a median follow-up of 6 years. For this analysis, patients with biopsy-proven lupus nephritis and at least 3 years of follow-up were included (n=56). Frequency and duration of renal flares were compared between patients who never developed CKD (n=29) and patients who developed new CKD (n=12) and between patients with preexisting but stable CKD (n=7) and patients who progressed (n=8). Groups were also combined into good (no CKD and stable CKD) or poor (new CKD and progressive CKD) for analysis. RESULTS: The new CKD group had more renal flares per year compared with the no CKD group (median=0.56 flares/yr [range=0–2] versus median=0 flares/yr [range=0–1.4]; P<0.001). Additionally, the poor outcome group had more renal flares per year compared with the good outcome group (median=0.50 flares/yr [range=0–2] versus median=0 flares/yr [range=0–1.4]; P<0.001). New or progressive CKD was not preferentially associated with nephritic compared with proteinuric renal flares. Logistic regression showed that spending more than 30% of time in renal flare (odds ratio, 20; 95% confidence interval, 4.6 to 91.3; P<0.001) and age>35 years (odds ratio, 69; 95% confidence interval, 6.3 to 753.6; P<0.001) were independent predictors of the combined end point of developing new or progressive CKD. All four subjects over 35 years of age that spent over 30% of time in renal flare had a poor outcome. CONCLUSION: In patients with lupus nephritis, the relative duration of renal flare is an independent predictor of incident and progressive CKD.